The implications of different ethnicity categorisation methods for understanding outcomes and developing policy in New Zealand. (2nd January 2020) - Boven, Natalia; Exeter, Daniel; Sporle, Andrew; Shackleton, Nichola
ABSTRACT: Identifying with more than one ethnicity is becoming increasingly common in New Zealand. It is therefore important that the methods of categorising ethnicity used by government agencies and researchers effectively account for diverse ethnic identities. The aim of this research was to assess the impact of using different methods of categorising ethnicity on understanding outcomes in New Zealand, using Census 2013 information about tobacco smoking among the population aged 15+ years as an illustration. Prioritised, total response and single/combination categorisation methods were compared. Prioritised and total response categorisation generally produced similar prevalence estimates and patterns for smoking status, although estimates diverged somewhat for Māori ethnic groups and to a lesser extent for Pacific Peoples and Asian ethnic groups. Single/combination categorisation indicated that combination ethnic groups tend to have smoking outcomes between those of the constituent groups. Categorisation method had a considerable impact on the size of some ethnic groups. Prioritised ethnicity categorisation may be inappropriate for use by government agencies and for policy-relevant research principally concerned with children, young people, Māori or Pacific Peoples. Single/combination categorisation is useful for understanding the associations between ethnicity and outcomes, however previous work suggests this method should be used with caution.